1971
DOI: 10.3109/00498257109033172
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Azo Reduction byStreptococcus faecalisII. The Role of Soluble Flavins

Abstract: 1. Using a previously developed continuous assay system, the mechanism of stimulation of Red 2G azo reduction in Streptococcus fueculis by additions of soluble flavins has been investigated.2. Reduced flavins acting as two-electron donors can rapidly reduce Red 2G non-enzyniically and the reduced flavins can act as an electron shuttle from NAD(P)H-dependent flavoproteins to the acceptor azo compound.3. Results of inhibition studies were consistent with the direct participation of soluble flavins and the non-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(58 citation statements)
references
References 17 publications
0
57
0
1
Order By: Relevance
“…This activity, however, cannot be attributed to the catalase-peroxidase previously isolated from this organism, which did not attack any of the tested dyes (13). An intracellular azoreductase (EC 1.7.1.6 [azobenzene reductase]) is responsible for the decolorization activity, as previously shown for other azo-dye-degrading microorganisms (11,31,36). Two bands showing azoreductase activity were found after separation of the cell lysate from Bacillus strain SF in gels combined with activity staining.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This activity, however, cannot be attributed to the catalase-peroxidase previously isolated from this organism, which did not attack any of the tested dyes (13). An intracellular azoreductase (EC 1.7.1.6 [azobenzene reductase]) is responsible for the decolorization activity, as previously shown for other azo-dye-degrading microorganisms (11,31,36). Two bands showing azoreductase activity were found after separation of the cell lysate from Bacillus strain SF in gels combined with activity staining.…”
Section: Discussionmentioning
confidence: 59%
“…In contrast, under anaerobic conditions, the decolorization of many azo dyes via reduction of the azo bond has been shown for anaerobic (e.g., Bacteroides sp., Eubacterium sp., and Clostridium sp.) as well as facultative anaerobic (e.g., Proteus vulgaris and Streptococcus faecalis) bacteria (5,11,30,36). The main interest in this field has been focused on bacteria from the human intestine that are involved in the metabolism of azo dyes ingested as food additives (9).…”
mentioning
confidence: 99%
“…A description of a nonspecific azo reductase system involved in azo dye reduction has been provided for selected bacterial species, and it has been shown that the MICROBIAL POPULATIONS TREATING DYE EFFLUENT 3231 relevant gene is relatively conserved in various anaerobic and facultative bacteria (24,46). Redox mediator compounds, such as flavins, have been shown to enhance degradation of azo dyes by acting as electron shuttles that facilitate reduction of the azo dye (13). In this research it was also hypothesized that coenzyme reducing equivalents involved in normal electron transport through oxidation of organic substrates may act as electron donors for reduction of azo dyes.…”
Section: Discussionmentioning
confidence: 99%
“…A physiological role for azo reduction, as an electron sink during anaerobic growth, has been suggested for Ent. faecalis [47]. The ability to dispose of excess reducing power in this way would be energetically favourable to fermentative bacteria growing in the large gut.…”
mentioning
confidence: 99%